Deposit Insurance around the World : A Comprehensive Database - Demirgüç-Kunt, Asli (World Bank, Washington, DC, 2012)
This paper updates the Demirguç-Kunt and Sobaci (2001) cross-country deposit insurance database and extends it in several important dimensions. This new data set identifies both recent adopters and the ones that were not covered earlier due to a lack of data. Moreover, for the first time, it provides historical time series for several variables and adds new ones. The data were collected by surveying deposit insurance institutions and related agencies as well as through the use of various other country sources.